Essential oil composition of Aloysia triphylla (L'Herit) Britton leaves cultivated in Botucatu, São Paulo, Brazil - De Figueiredo, Roseane O. [UNESP]; Stefanini, Mirian B.; Ming, Lin Chau; Marques, Márcia Ortiz Maio; Facanali, Roselaine (My University, 2004)
The family Verbenaceae comprises about 175 genera and 2300 species, distributed in tropics and subtropics, mainly in temperate zone of southern hemisphere. The lemon verbena (Aloysia triphylla (L'Herit) Britton) is a perennial, bushy plant originally from South America. The essential oil of this plant is used in pharmaceutical, cosmetic and perfumery industry. Therapeutic properties include febrifuge, sedative, stomachical, diuretic, and antispasmodic activities. The present work aimed to identify the chemical composition of essential oil of Aloysia triphylla leaves. The study was done in Lageado Experimental Farm of the Department of Plant Production-Horticulture, Agronomical Sciences College, São Paulo State University Campus of Botucatu. Leaves of lemon verbena from Medicinal and Aromatic Plant Garden, were collected in the end of winter (September/2001). The essential oil was extracted by hydrodistillation, in Clevenger apparatus. 100 g of leaves were used in each extraction. Four extractions were performed during three hours. The essential oils of the leaves were analyzed in Gas Chromatography Mass spectrometry (CG-MS, Shimadzu, QP-5000), equipped with capillary column DB-5 (30 m × 0,25 mm × 0,25 mm), split 1/35, injector for 220 C°, detector for 230 C°, dragged by gas He (1,0 mL/min), with programmed temperature for 60 C° to 240 C°, 3 C°/min. The identification of the substances was held by comparison of their mass spectra with data of the CG-MS (Nist 62 lib), literature references and retention index of Kovats. The main constituents of essential oils were geranial (29.54 %), neral (27.01 %), limonene (15.93 %), geranyl acetate (4.0 %) and geraniol (3.96 %). This species possesses high quantity of monoterpenes and low quantity of sesquiterpenes.
Keywords: Aloysia triphylla; Medicinal plants; Phytochemistry; Verbenaceae